Blutaparon portulacoides ethanolic extract reduced IL-1β and inflammatory parameters induced by the Mycobacterium complex and carrageenan in mice - Kassuya, Roberto Mikio; Radai, Joyce Alencar Santos; Macorini, Luis Fernando Benitez; Nunes, Viktor Krejci; Salvador, Marcos José; Leite, Patricia Regina Terço; Oliveira, Rodrigo Juliano; Croda, Júlio; Arena, Arielle Cristina [UNESP]; Kassuya, Cândida Aparecida Leite (Springer Nature, 2020)
Information on the health benefits of ethanolic extracts obtained from Blutaparon portulacoides stem (EEBP) hasn´t been consistently described in the literature until the present moment. This study investigated the antimycobacterial, anti-inflammatory and toxicological effects of EEBP in models of inflammation/infection, as well as its chemical composition. Chemical analysis of EEBP by electrospray ionization–mass spectrometry/HPLC–MS/MS identified 3,5,3′-Trihydroxy-4′-methoxy-6,7-methylenedioxy-flavone, gomphrenol, ferulic, vanillic, and caffeic acids. The minimum inhibitory concentration of EEBP and isoniazid in the presence of Mycobacterium tuberculosis was 123.4 and 0.030 µg/ml, respectively. EEBP oral administration (p.o.) (300–1000 mg/kg) or dexamethasone subcutaneous injection (s.c.) (1 mg/kg) significantly inhibited leukocytes and proteins resulting from carrageenan-induced pleurisy in Swiss mice. In the BCG-induced pleurisy model, the oral treatments performed once a day for 7 days, with EEBP (30 and 100 mg/kg) and isoniazid (25 mg/kg), inhibited the increase in plasmatic IL-1β levels and in pleural exudate from C57BL-6 mice, and reduced M. tuberculosis growth in organs (colony forming units assays). EEBP (30–300 mg/kg, p.o.) and dexamethasone (1 mg/s.c.) significantly prevented carrageenan-induced oedema and mechanical hyperalgesia in Swiss mice. The treatments (once a day for 22 days) with EEBP (30 mg/kg, p.o.) and dexamethasone (1 mg/s.c.) substantially inhibited oedema and mechanical- and cold-hyperalgesia at 11, 16 and 22 days after the administration of Freund's Complete Adjuvant in C57bL6 mice. No evidence of physio-pathologic was observed in Wistar rats acutely treated with EEBP (2000 mg/kg, p.o.). This study confirms the anti-inflammatory and antibiotic properties of EEBP, opening possibilities for the development of safe new drugs with dual anti-inflammatory/antimycobacterial activities which could be favorable from a pharmacoeconomic perspective.
Keywords: Amaranthaceae; Blutaparon portulacoides; Inflammation; Mycobacterium tuberculosis